Pedagogic Competence of PAI Teachers in the Implementation of the Merdeka Curriculum - M Saipul Watoni; Alfan Hadi; Eniza (Journal of Educational Studies, 2025)
The implementation of the Merdeka Curriculum in Indonesia demands teachers to possess strong pedagogic competence characterized by student-centered instruction, adaptive planning, and integration of character values. This study aims to analyze the pedagogic competence of Islamic Education (PAI) teachers in implementing the Merdeka Curriculum, focusing on nine competence indicators: understanding student characteristics, lesson planning, learning implementation, assessment design, utilization of media and technology, classroom management, contextual learning integration, reflective teaching, and character and Pancasila Profile development. This research employed a mixed descriptive approach, combining rubric-based assessment, documentation analysis, classroom observation, and teacher self-reflection questionnaires. Three PAI teachers at RA Al Hikmah NW Batu Rimpang were evaluated by school leaders using a standardized rubric and further interviewed to explore challenges and pedagogical practices. The results show that PAI teachers demonstrate a high level of pedagogic competence with an overall score of 3.28. Teachers excel in lesson planning and character development, particularly in integrating Islamic values with the Pancasila Student Profile through contextual, ethical, and collaborative learning activities. However, the findings also reveal that teachers have not fully maximized reflective teaching and digital pedagogical competence due to insufficient training and limited use of interactive learning platforms. These limitations affect digital assessment practices and weaken data-driven instructional improvement. The study implies the need for structured mentoring in reflective teaching and professional development focused on digital pedagogy. This research recommends strengthened institutional support, technological resources, and longitudinal monitoring to optimize PAI teacher competence in implementing the Merdeka Curriculum.